Comparative Analysis of Fracture Resistance in Teeth Obturated with Graphene Oxide-Modified Sealers - Jasmine Marwaha; Divya Batra; Deepankar Dass; Shivani Parmar; Ashtha Arya; Ataul Hafeez Imran (Journal of Pharmacy and Bioallied Sciences)
Background: For long-term success, endodontically treated teeth must be resistant to fracture. The creation of new materials with potential mechanical qualities, such sealers modified with graphene oxide, might increase the longevity of obturated teeth. The purpose of this research is to examine the fracture resistance of teeth that have been sealed using traditional sealers versus sealers modified with graphene oxide. Materials and Methods: Using the ProTaper Gold rotary device, thirty recently removed mandibular premolars were prepped and decoronated to standardize root length. Three groups of 10 samples each were randomly selected: Group 1 was the control group, which did not have any obturation; Group 2 was the group that had teeth sealed with a traditional bioceramic sealer; and Group 3 was the group that had teeth sealed with a sealer modified by graphene oxide. The lateral compaction method was used to fill each root with gutta-percha. To replicate oral circumstances, the samples underwent 500 cycles of thermocycling between 5°C and 55°C. A universal testing machine was used to test for fracture resistance, exerting compressive force at a crosshead speed of 1 mm/min till failure. Results: The following were the average fracture resistance values: 300 N ± 25 N was the value for Group 1 (control), 450 N ± 30 N for Group 2 (traditional sealer), and 550 N ± 35 N for Group 3 (graphene oxide-modified sealer). Group 2 had superior resistance than Group 1 (P < 0.05), whereas Group 3’s fracture resistance was substantially higher than that of Groups 1 and 2 (P < 0.05). Conclusion: When compared to traditional sealers, graphene oxide-modified sealers greatly increase the fracture resistance of teeth that have had endodontic treatment. According to these results, graphene oxide may be a useful supplement for enhancing the endodontic sealers’ mechanical qualities.